Complete resection of an anterior mediastinal tumor by total arch replacement and pulmonary artery trunk plasty with a pericardial patch: A case report. (November 2018) - Chikaishi, Yasuhiro; Matsumiya, Hiroki; Kanayama, Masatoshi; Taira, Akihiro; Nabe, Yusuke; Shinohara, Shinji; Kuwata, Taiji; Takenaka, Masaru; Oka, Soichi; Hirai, Ayako; Kuroda, Koji; Imanishi, Naoko; et al.
Abstract: Introduction: Patients with undiagnosed anterior mediastinal tumors commonly undergo surgery for diagnosis and treatment. However, determining the optimal therapeutic strategy is difficult for tumors with substantial invasion, such as lesions touching the aortic arch (AA). Case presentation: A 76-year-old man of Asian descent presented to our hospital because chest computed tomography (CT) revealed an anterior mediastinal tumor. This tumor surrounded the left subclavian vein and touched the AA. We suspected the tumor to be malignant. We therefore decided to resect the tumor with preparation for total arch replacement (TAR). The operation was performed in three steps. First, we performed a mediastinal sternotomy. However, the tumor had invaded the subclavian vein, so we resected this vein after adding a transmanubrial approach. However, because of invading the AA we needed next step. Second, we shifted the patient to the right lateral decubitus position. We performed partial resection of the left upper lobe and exfoliated the distal AA. Third, we shifted the patient to the dorsal position and implanted an artificial cardiopulmonary device, after which we performed TAR, and pulmonary artery (PA) trunk plasty with a pericardial patch. The operation was successful, with no major adverse events. Pathologically, the tumor was diagnosed as diffuse large B-cell lymphoma. Discussion: If oncologically complete resection is preferable for tumors with substantial invasion, complete resection should be attempted even if the surgery is difficult. Conclusion: We performed complete resection of an anterior mediastinal tumor with TAR and PA trunk plasty using a pericardial patch. Highlights: We performed complete resection of a malignant tumor through TAR and PA trunk plasty with a pericardial patch. Discrimination between ML and thymoma is frequently difficult. If complete resection is preferable for tumors, the surgery should be attempted even if the surgery is difficult.